THE CURRENT STATUS OF STRESS, ANXIETY, DEPRESSION AND SOME RELATED FACTORS AMONG STUDENTS OF HON GAI HIGH SCHOOL, HA LONG WARD, QUANG NINH PROVINCE IN 2026 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of stress, anxiety, and depression among students at Hon Gai High School in 2026 using the DASS-21 scale and to investigate some related factors.Method: A descriptive cross-sectional study with analysis was conducted on 590 students in grades 10-12 at Hon Gai High School in 2026. Data were collected using a questionnaire incorporating the DASS-21 scale. Stress, anxiety, and depression were described according to the DASS-21 standard thresholds; associations were investigated using univariate and multivariate logistic regression.Results: The percentages of students experiencing stress, anxiety, and depression were 22.9%, 28.1%, and 16.6%, respectively. Stress was independently associated with female gender, less than 6 hours of sleep per day, being scolded or punished by parents/relatives, and exam/test pressure. Anxiety is independently associated with less than 6 hours of sleep per day, exam/test pressure, witnessing parental arguments, and little or no attention from friends. Depression is independently associated with less than 6 hours of sleep per day, exam/test pressure, dissatisfaction with friendships, and little or no attention from friends.Conclusion: Stress, anxiety, and depression among high school students in Hon Gai are significant concerns, especially anxiety. Lack of sleep, academic pressure, unfavorable family environments, and lack of social support from peers are all linked to mental health problems in students. Increased early screening, school psychological counseling, and coordination between schools, families, and school health services are necessary.
Keywords: high school students, stress, anxiety, depression, DASS-21, school mental health.